DNA binding and cleavage modes of shishijimicin A - Zhang, Hao (2021)
Although shishijimicin A and its extreme potencies against an array of cancer cell lines have been known for more than a decade, its assumed DNA-cleaving mechanism has not been substantiated as yet. Herein we report studies that reveal binding and scission of double-stranded DNA by shishijimicin A. The results of these studies support the proposed hypothesis that DNA strand scissions are caused by 1,4-benzenoid diradicals formed by Bergman cycloaromatization of the enediyne core of shishijimicin A upon activation by thiols. In addition, double-stranded supercoiled DNA-cleavage experiments with shishijimicin A in competition with known minor groove binders, UV spectroscopic studies, and electrophoretic analysis were utilized to clarify the binding mode of the molecule to DNA. These investigations indicate that shishijimicin A binds to the minor groove of double-stranded DNA and that its β-carboline moiety plays a role in the binding through intercalation. In addition, due to the fact that naked linker regions of DNA in the interphase and metaphase of eukaryotic cells are unprotected by histone proteins during entire cell cycles and because these unprotected regions of DNA are vulnerable to attack by DNA binders, it was concluded that the observed double-strand DNA cleavage and very low sequence selectivity by shishijimicin A may account for its extraordinary cytotoxicity.